Wall characteristics and mechanisms of ischaemic stroke in patients with atherosclerotic middle cerebral artery stenosis: a high-resolution MRI study. (2nd July 2016) - Zhao, Deng-Ling; Deng, Gang; Xie, Bo; Gao, Bo; Peng, Cheng-Yu; Nie, Fang; Yang, Ming; Ju, Shenghong; Teng, Gao-Jun
Abstract : Objective:: To evaluate the characteristics of atherosclerotic middle cerebral artery (MCA) stenosis by high-resolution magnetic resonance imaging (HR-MRI) and determine the relationship between wall characteristics and infarction patterns. Methods:: Thirty-six patients with acute ischaemic stroke due to MCA stenosis underwent diffusion-weighted magnetic resonance imaging (DWI) and HR MRI. Wall characteristics of MCA, including irregular surface, superior location, T2-hyperintense of plaques and positive remodelling (PR), were analysed. Characteristics of acute infarct on DWI were categorised according to the number (single or multiple infarcts) and the pattern of cerebral infarcts (cortical, border zone or perforating artery territory infarcts). The relationship between wall characteristics and infarction patterns was evaluated. Results:: PR was observed in 20 patients, irregular surface plaque in 18 patients, superior location of plaques in 14 patients and T2-hyperintense foci in 13 patients. Seventeen patients had multiple acute cerebral infarcts and 13 showed single acute cerebral infarcts. Border zone infarcts were the most common (76.5%) among multiple acute infarcts. Penetrating artery infarcts (PAI) accounted for 76.9% of all single infarcts. Multiple infarcts were more frequently observed in patients with PR ( P =  0.007) or plaque surface irregularity ( P =  0.035). Single infarcts, especially PAI, were more prevalent in patients with superior plaque ( P =  0.030). No statistically significant differences were observed between multiple and single infarcts in patients with T2-hyperintense lesions ( P  = 0.638). Conclusions:: PR or irregular surface plaques were associated with artery-to-artery embolism. Superior location of plaques was associated with PAI. HR-MRI provides insights into intracranial atherosclerosis in vivo, predictive of infarction patterns.